The system of administration of justice of the communal peasant rounds: The case of the peasant rounds of the Huancarmayo and Huarahuaramayo basins - Aranda, Mirva (2002)
In the department of Cusco, the peasant patrols are communal, that is, they form part of the community structure. There are communal patrols in six provinces of Cusco: Quispicanchi, Chumbivilcas, Paucartambo, Canas, Espinar and Canchis.